Analysis of the Influence of Raw Material Types for Clothing on the Level of Consumer Interest Aged 18-22 Years in Brand XYZ - Nugraha, Isna; Kirana, Intania Widyantari; Khofiyah, Nida An; Ramadhan, Gilang (Tekmapro, 2025)
Brand XYZ is a global apparel company that emphasizes comfort, durability, and design aesthetics in its product offerings. This study aims to examine the influence of clothing material type on purchase interest among consumers aged 18–22 years. A quantitative research approach was applied, using data collected from 50 respondents via a structured questionnaire on a 5-point Likert scale. Statistical analyses were performed using SPSS, including the Kolmogorov–Smirnov test for normality, a linearity test, Pearson correlation analysis, and simple linear regression. The results show that the data met the normality assumption (p = 0.859) and revealed a strong positive correlation between clothing material type and purchase interest (r = 0.810, p < 0.001). The regression model was found to be significant (F = 91.728, p < 0.001) with the equation Y=1.932+0.859XY = 1.932 + 0.859XY=1.932+0.859X and an R2R^2R2 value of 0.656, indicating that 65.6% of the variance in purchase interest can be explained by the clothing material type. The findings highlight the critical role of material selection in influencing consumer behavior. Practical recommendations for Brand XYZ include diversifying high-quality material options, improving transparency in fabric information, and implementing targeted consumer education campaigns to enhance brand loyalty and purchase intention.